2015
DOI: 10.3171/2015.5.peds15157
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative ultrasound localization of the lambda in patients with scaphocephaly: a technical note for minimally invasive craniectomy

Abstract: Sagittal craniosynostosis, the most common single suture craniosynostosis, is treated by numerous surgical techniques. Minimally invasive endoscopy-assisted procedures with postoperative helmeting are being used with reports of good cosmetic outcomes with decreased morbidity, shortened hospital stay, and less blood loss and transfusion. This procedure uses small skin incisions, which must be properly placed to provide safe access to the posterior sagittal and lambdoid sutures. However, the lambda is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Most studies included were retrospective in design, whereby two authors [ 28 , 44 ] reported on their prospectively analyzed sample. The number of patients presented varied between 5 and 256 [ 6 , 28 , 35 ]. In total, 885 children with isolated sagittal suture craniosynostosis were included, wherein 188 were female and 537 male (sex was only specified in 10 articles, 725 included patients respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies included were retrospective in design, whereby two authors [ 28 , 44 ] reported on their prospectively analyzed sample. The number of patients presented varied between 5 and 256 [ 6 , 28 , 35 ]. In total, 885 children with isolated sagittal suture craniosynostosis were included, wherein 188 were female and 537 male (sex was only specified in 10 articles, 725 included patients respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Nine series stated their procedures were carried out by a single neurosurgeon [ 8 , 22 , 24 , 25 , 28 , 32 , 33 , 38 , 47 ]. In 2 series, the decision for one or more additional craniofacial/plastic surgeons or an accompanying pediatric neurosurgery fellow to participate depended on the severity of the underlying pathology [ 6 , 35 , 37 , 44 ]. An anesthesiologist was mentioned to work solely for the group, responsible as a pediatric specialized member, in 2 reports [ 8 , 35 ].…”
Section: General Considerationsmentioning
confidence: 99%
“…Average operating time was 87 min and mean blood loss was 32 cm 3 . We encountered small durotomies in a single patient requiring primary repair.…”
Section: Discussionmentioning
confidence: 99%
“…In small infants with scaphocephaly, however, palpation of the lambdoid suture through the skin can be challenging, which can lead to imperfect incision placement and morbidity. Techniques have been described to attempt to mitigate this challenge with ultrasound guidance [3]. To circumvent this issue entirely, we employed a single-incision technique that allows the surgeon to approach the lambdoid suture internally and identify it directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation